Analysis of Nurse and Midwife Job Satisfaction on Training Programs, Provision of Welfare and Implementation of Position Promotion at Royal Prima Marelan Hospital - Leony, Catherine; Ginting, Chirmis Novalinda; Chiuman, Linda (Fakultas Kedokteran Universitas Malikussaleh, 2023)
Feelings of satisfaction at work can have a positive impact on behavior, such as discipline, morale, and loyalty. Job satisfaction is the key to the productivity of an organization, especially health services. In fact, job satisfaction and well-being of health workers play an important role in the quality of health services. Nurse jobsatisfaction is related to nurse performance, service quality, and increased patient satisfaction. The purpose of this study was to analyze the job satisfaction of nurses and midwives with training programs, providing welfare and implementing promotions at RSU Royal Prima Marelan. The sample in this study were 76 nurses and midwives at RSU Royal Prima Marelan with the sampling technique using total sampling. The analysis used in this study was univariate, bivariate and multivariate analysis. The results of this study indicate that there is an effect of the training program on the job satisfaction of nurses and midwives at RSU Royal Prima Marelan. There is an effect of providing welfare on the job satisfaction of nurses and midwives at RSU Royal PrimaMarelan. There is an effect of implementing promotion on the job satisfaction of nurses and midwives at RSU Royal Prima Marelan. There is an influence of training programs, provision of welfare and implementation of promotion on the job satisfaction of nurses and midwives at RSU Royal Prima Marelan. The independent variable that has the most influence on the job satisfaction of nurses and midwives at RSU Royal Prima Marelan is the variable providing welfare. There is an influence of the influence of training programs, providing welfare and implementing promotion on the job satisfaction of nurses and midwives at RSU Royal Prima Marelan.